2018
DOI: 10.1038/s41598-018-32451-w
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Human Immunodeficiency Virus Type-1 Latency in Primary Human Monocyte-Derived Macrophages Induced by Sustained M1 Polarization

Abstract: We have reported that short-term stimulation of primary human monocyte-derived macrophages (MDM) with interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α), i.e. M1 polarization, leads to a significant containment of virus replication. Here we show that M1-MDM restimulation with these cytokines 7 days after infection (M12 MDM) promoted an increased restriction of HIV-1 replication characterized by very low levels of virus production near to undetectable levels. In comparison to control and M1-MDM that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 63 publications
4
25
0
Order By: Relevance
“…Our data demonstrate that interactions between macrophages and pathogenic or commensal microorganisms within the genitourinary and gastrointestinal tracts, such as GC and E. coli, may alter the ability of macrophages to serve as reservoirs for viral persistence in the host. Our findings are consistent with independent studies that demonstrate that repeated stimulation of M1-polarized MDMs with proinflammatory cytokines (TNF-α) and/or type II IFNs (interferon-γ) induce a state akin to HIV-1 latency (85). In addition, the oral pathogen Porphyromonas gingivalis has been shown to influence the establishment and maintenance of persistent HIV-1 infection in MDMs (86).…”
Section: Discussionsupporting
confidence: 93%
“…Our data demonstrate that interactions between macrophages and pathogenic or commensal microorganisms within the genitourinary and gastrointestinal tracts, such as GC and E. coli, may alter the ability of macrophages to serve as reservoirs for viral persistence in the host. Our findings are consistent with independent studies that demonstrate that repeated stimulation of M1-polarized MDMs with proinflammatory cytokines (TNF-α) and/or type II IFNs (interferon-γ) induce a state akin to HIV-1 latency (85). In addition, the oral pathogen Porphyromonas gingivalis has been shown to influence the establishment and maintenance of persistent HIV-1 infection in MDMs (86).…”
Section: Discussionsupporting
confidence: 93%
“…Primary MDMs stimulated IFNγ and TNFα into an M1 phenotype show viral containment and inhibition of viral replication and integration upon re-stimulation to an M1 phenotype. These M1-double stimulated MDMs have an upregulation in APOBEC3A and APOBEC3G restriction factors as well as negative regulators of proviral transcription, which assisted in keeping the replication-competent virus in a latent state ( Graziano et al, 2018 ).…”
Section: Macrophage Biology Hiv-1 Infection and Cellular Reservoirsmentioning
confidence: 99%
“…Macrophages favor retention of accumulated viral particles contained in VCC, triggering release through stimulation or cell necrosis or apoptosis. Upon stimulation by microenvironmental factors like extracellular ATP, macrophages are triggered to rapidly release infectious virions from VCCs ( Graziano et al, 2018 ). Additionally, bone marrow stromal cell antigen 2 (BST2) has been found contained in VCCs with HIV-1 virions, tethering HIV-1 virions to the cell membrane or these VCCs.…”
Section: Macrophage Biology Hiv-1 Infection and Cellular Reservoirsmentioning
confidence: 99%
“…Secondly, it acts as a transcriptional repressor of both basal and stimulated HIV-1 transcription induced by phorbol ester plus ionomycin, by preventing the binding of the cellular transcription factor Sp1 to HIV-1 promoter [42, 43]. Furthermore, we recently demonstrated that TRIM22 cooperates with the MHC Class II trasactivator (CIITA) to inhibit transcription initiation and elongation of the viral genome [44, 45] strongly suggesting that the combined action of the two factors may not only restrict viral replication but also potentially contribute to the establishment of viral latency [46, 47]. Besides inhibiting HIV-1 transcription, TRIM22 also inhibits Influenza A virus [48], Hepatitis B and C viruses [49, 50] and encephalomyocarditis virus [51], by using different mechanisms.…”
Section: Hiv-1 Restriction Factorsmentioning
confidence: 99%